Frequency patterns of core constipation symptoms among the Asian adults: a systematic review - Abdul Wahab, Patimah; Yeong, Yeh Lee; Mohd Yusoff, Dariah (BioMed Central, 2017)
Background: In clinical practice, assessment of constipation depends on reliability, consistency and frequency of several commonly reported or core symptoms. It is not known if frequency patterns of constipation symptoms in adults are different between the West and the East. This review aimed to describe core constipation symptoms and their frequency patterns among the Asian adults. Methods: Articles published in PubMed, MEDLINE, CINAHL and Science Direct from 2005 to 2015 were searched systematically. Studies were included if constipation satisfied the Rome II and or III criteria. Study populations consisted of Asian adults above 18 years old and with sample size above 50. Results: Of 2812 articles screened, 11 met the eligibility criteria. Constipation among Asian adults was characterized by three core symptoms of ‘straining’ at 82.8%, ‘lumpy and hard stool’ at 74.2% and ‘sensation of incomplete evacuation’ at 68.1% and the least frequent symptom was ‘manual maneuver to facilitate defecation’ at 23.3%. There was heterogeneity in frequency patterns of core symptoms between different Asian studies but also differences in core symptoms between constipation subtypes of functional constipation and irritable bowel syndrome with constipation. Conclusions: In general, Asian adults perceive constipation symptoms in a similar but not equivalent manner to the West. Recognition of core symptoms will increase the diagnostic confidence of constipation and its subtypes but more studies of the various specific Asian populations are needed to address their differences.